Kant’s Concept of Genius: A Defence, Against Romanticism and Scepticism - Hamilton, Andy (Aesthetica Preprint, 2021)
This article defends a Kantian conception of genius, as a middle way between the Romantic, and the Nietzschean sceptical conceptions. It begins by considering how the concept of genius has evolved, before addressing how Kant’s account of genius helps resolve a tension within his aesthetics between aesthetic judgment as appreciation of purposiveness without a purpose, and recognition that the artwork is created purposefully. It considers the relation of genius to rule-following and the exemplary. It concludes with a defence of the concept of genius as well-defined, against contemporary critiques which see it as elitist, patriarchal, ethnocentric and mystificatory. In his discussion, I argue, Kant relates talent, skill and the exemplary in an elucidatory explanatory holism.